2019
DOI: 10.1111/dmcn.14343
|View full text |Cite
|
Sign up to set email alerts
|

Health care service for families with children at early risk of developmental delay: an All Our Families cohort study

Abstract: Aim This study examined children’s health care service use, mothers’ workforce participation, and mothers’ community engagement based on children’s risk of developmental delay. Method We used data from the All Our Families study, a prospective pregnancy cohort. Ages and Stages Questionnaire (ASQ) scores at year 2 indicated risk of developmental delay. To investigate the impact of risk of developmental delay when children were not diagnosed, a sensitivity analysis excluded reports of neurodevelopmental disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…require a diagnosis before services are offered, early identification is key to accessing these services. As one possible solution to this issue, screening tools may increase early identification; 29 however, thoughts are mixed on screening tools and how to best use them. 30,31 In addition, relaxing the requirements for diagnosis and providing services when a demonstrable need is seen (i.e.…”
Section: Eligibilitymentioning
confidence: 99%
“…require a diagnosis before services are offered, early identification is key to accessing these services. As one possible solution to this issue, screening tools may increase early identification; 29 however, thoughts are mixed on screening tools and how to best use them. 30,31 In addition, relaxing the requirements for diagnosis and providing services when a demonstrable need is seen (i.e.…”
Section: Eligibilitymentioning
confidence: 99%
“…Therefore, early childhood development is closely related to a child's later health and wellbeing (Lu et al, 2016). Both developmental delays and chronic health conditions increase health service utilization (e.g., hospitalization, and visits to physicians) (Arim et al, 2017;Gallaher et al, 2002;Russell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of suspected DD for ECDI for Nepal was 35.1% among children aged 36–59 months [ 14 ]. Healthcare costs associated with children who are at risk of delayed development have been found to be higher than those who are not at risk [ 15 ]. A follow-up study found that the majority of the children who were identified to be developmentally delayed at 3 years of age were either under or unemployed, living along with family and financially dependent upon their families and socially isolated [ 16 ].…”
Section: Introductionmentioning
confidence: 99%